Influence of Menisci on Tibiofemoral Contact Mechanics in Human Knees: A Systematic Review - Sukopp, Matthias; Schall, Florian; Hacker, Steffen P.; Ignatius, Anita; Dürselen, Lutz; Seitz, Andreas M. (Frontiers in Bioengineering and Biotechnology, 2021)
Purpose: Menisci transfer axial loads, while increasing the load-bearing tibiofemoral contact area and decreasing tibiofemoral contact pressure (CP). Numerous clinical and experimental studies agree that an increased CP is one predominant indicator for post-traumatic osteoarthritis (PTOA) of the knee joint. However, due to the immense variability in experimental test setups and wide range of treatment possibilities in meniscus surgery, it is difficult to objectively assess their impact on the CP determination, which is clearly crucial for knee joint health. Therefore, the aim of this systematic review is to investigate the influence of different meniscal injuries and their associated surgical treatments on the CP. Secondly, the influence of different test setups on CP measurements is assessed. On the basis of these results, we established the basis for recommendations for future investigations with the aim to determine CPs under different meniscal states. Methods: This review was conducted in accordance with the PRISMA guidelines. Studies were identified through a systematic literature search in Cochrane, PubMed and Web of Science databases. Literature was searched through pre-defined keywords and medical subject headings. Results: This review indicates a significant increase of up to 142% in peak CP when comparing healthy joints and intact menisci with impaired knee joints, injured or resected menisci. In addition, different test setups were indicated to have major influences on CP: The variety of test setups ranged from standard material testing machines, including customized setups via horizontal and vertical knee joint simulators, through to robotic systems. Differences in applied axial knee joint loads ranged from 0 N up to 2700 N and resulted unsurprisingly in significantly different peak CPs of between 0.1 MPa and 12.06 MPa. Conclusion: It was shown that untreated traumatic meniscal tears result in an increased CP. Surgical repair intervention were able to restore the CP comparable to the healthy, native condition. Test setup differences and particularly axial joint loading variability also led to major CP differences. In conclusion, when focusing on CP measurements in the knee joint, transparent and traceable in vitro testing conditions are essential to allow researchers to make a direct comparison between future biomechanical investigations.